Development of a Low-Cost Device for Respiratory Frequency Measurement and Anomaly Detection - Raymundo, Carlos (2024)
The respiratory frequency monitoring is essential in medical environments to assess the lung health of patients. This work introduces a low-cost device designed to measure respiratory frequency in an automated manner and detect potential anomalies. The device provides accurate measurements, freeing medical staff from manual tasks. In addition to its application in hospitals, the device is proposed as a valuable tool for home sleep monitoring, opening new possibilities for the early detection of conditions such as sleep apnea. It also allows for remote data transmission and integration with mobile devices. The respiratory signal was successfully compressed without losing its key characteristics, achieving a compression rate of over 95% and facilitating storage and processing. In summary, this device aims to enhance efficiency in respiratory frequency monitoring, offering a low-cost solution with a significant impact on healthcare and the patient’s quality of life.